Spring Lane, ca. 1895 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west of buildings lining Spring Lane, located between Washington Street to the west-northwest and Devonshire Street to the east. Signage adorns the facades and elevations of the buildings included in the photograph. A street light is located on the sidewalk lining the north side of Spring Lane, while another street light is attached to the facade of 5 Spring Lane, located on the south side of the street. Several men and boys fill Spring Lane. 7 3/4 x 5 7/8 Photographs